Prevalence and Molecular Mechanisms of Carbapenem Resistance among Gram-Negative Bacilli in Three Hospitals of Northern Lebanon - Mariam Rima; Saoussen Oueslati; Laura Dabos; Dina Daaboul; Hassan Mallat; Elie Bou Raad; Marcel Achkar; Osman Mawlawi; Sandrine Bernabeu; Rémy A. Bonnin; Delphine Girlich; Marwan Osman; et al. (MDPI AG, 2022)
Carbapenem resistance (CR) is an emerging health issue. Epidemiological surveys on carbapenem-resistant Gram-negative bacilli (CR-GNB) in Lebanon remain scarce. In this study, we determined the prevalence of CR-GNB isolated between 2015 to 2019 in three hospitals in northern Lebanon: 311 CR-Enterobacterales (out of 11210; 2.8%), 155 CR-Pseudomonas (out of 1034; 15%) and 106 CR- Acinetobacter (out of 184; 57.6%) were identified. CR mechanisms were determined for 146 randomly chosen isolates: the Carba NP test revealed an enzymatic resistance to carbapenems in 109 isolates (out of 146, 74.7%). Produced carbapenemases were evaluated by the NG-Test Carba5, NG-Test OXA-23 immunochromatographic assays and PCR. Carbapenemase-producing (CP) Enterobacterales expressed blaOXA-48-like, blaNDM-like and blaVIM-like genes and CP-Pseudomonas expressed blaIMP-like and blaVIM-like genes, whereas CP-Acinetobacter expressed blaOXA-23-like genes. The NG-Test Carba5 results were confirmed by PCR sequencing and revealed several variants, such as NDM-19, VIM-62 and OXA-162, never described so far in Lebanon. Isolates with discordant results were sequenced by WGS and highlighted novel variants of the natural oxacillinases of Pseudomonas aeruginosa: blaOXA-50-like genes. Their role in carbapenem resistance should be further studied. Overall, our findings highlight an alarming situation and encourage health care centers to establish performant registration systems that could help in limiting resistance spread.